‘Flexing’ and its Implications for Religious and Social Life Among Indonesian Muslim Millennials - Rachman, Abdul; Sangare, Bilaly; Suardi, Didi; Jamaludin, Nur; Azwar, Martavevi; Simatupang, Aisyah Defy R.; Karim, Salman Izudin; Aprianto, Muhammad Rafli; Rizky, Teguh Muhammad (Cakrawala: Jurnal Studi Islam, 2024)
This study investigates the implications of the ‘flexing’ phenomenon, characterized by the ostentatious display of wealth and material possessions on social media, on the religious and social life of Indonesian Muslim millennials. Employing a qualitative research methodology, the study analyzes data collected through social media observation and interviews with millennial Muslims. Findings reveal that ‘flexing’ can have detrimental effects on religious life, including fostering excessive materialism, eroding integrity and honesty, and hindering the fulfillment of Islamic obligations such as Zakat and charitable giving. Furthermore, the study demonstrates that "flexing" contributes to social issues such as excessive consumerism, social inequality, a decline in empathy and concern for others, and potential mental health issues arising from social comparison and insecurity. The study concludes that while ‘flexing’ may be perceived differently by individuals, its potential negative impacts on religious values and social cohesion warrant critical consideration.